Visitor Notes: Jacob Biamonte − Categorical Models of Quantum Information in the Simulation of Many−Body Systems - Biamonte, J (Center for Quantum Technologies (CQT), 2010)
CQT attracts both long and short term visitors from all over the world. Jacob Biamonte, a Research Fellow at the University of Oxford and Lecturer in Physics at St Peter's College, explains the results of his two collaborative visits with several members of CQT staff, including Stephen Clark. Their work involved using higher mathematics to create a new theory of tensor network states and has numerous practical applications in the simulation of physical systems.